Islamic Religious Education Learning Experiences and Muslim Students’ Beliefs and Practices in Secondary Schools in Eastern Uganda - Maimuna Aminah Nimulola; Halima Wakabi Akbar (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2025)
We now live in an era where, believing in and doing certain things are regarded by some sections of society, including students and graduates of Islamic Religious Education (IRE) in Eastern Uganda, to be out of fashion and backward. Teachers of IRE are concerned about the inability of the subject to strengthen students’ faith and practice. But are their concerns justified, and if so, to what extent and under which contexts? This study sought to determine the influence of IRE learning experiences on Muslim students’ beliefs and practices. The population consisted of Senior Four and Six students from Eastern Uganda from which a sample of 890 was selected using multi-stage sampling. A questionnaire was used to collect data, which was analyzed using descriptive statistics, correlation and ANOVA. The relationship between students’ learning experiences and their beliefs was found not to be statistically significant; while that between learning experiences and their practices was statistically significant and moderate. A statistically significant difference in students’ practices among school types was also found, where students from Government Non-Muslim schools had the lowest while those from Private Islamic schools had the highest. It therefore is recommended that Islamic extra-curricular activities be organized for students to boost their knowledge and skills.